Genome Variation in Cryptococcus gattii, an Emerging Pathogen of Immunocompetent Hosts - C. A. D’Souza (American Society for Microbiology, 2011)
ABSTRACT Cryptococcus gattii recently emerged as the causative agent of cryptococcosis in healthy individuals in western North America, despite previous characterization of the fungus as a pathogen in tropical or subtropical regions. As a foundation to study the genetics of virulence in this pathogen, we sequenced the genomes of a strain (WM276) representing the predominant global molecular type (VGI) and a clinical strain (R265) of the major genotype (VGIIa) causing disease in North America. We compared these C. gattii genomes with each other and with the genomes of representative strains of the two varieties of Cryptococcus neoformans that generally cause disease in immunocompromised people. Our comparisons included chromosome alignments, analysis of gene content and gene family evolution, and comparative genome hybridization (CGH). These studies revealed that the genomes of the two representative C. gattii strains (genotypes VGI and VGIIa) are colinear for the majority of chromosomes, with some minor rearrangements. However, multiortholog phylogenetic analysis and an evaluation of gene/sequence conservation support the existence of speciation within the C. gattii complex. More extensive chromosome rearrangements were observed upon comparison of the C. gattii and the C. neoformans genomes. Finally, CGH revealed considerable variation in clinical and environmental isolates as well as changes in chromosome copy numbers in C. gattii isolates displaying fluconazole heteroresistance. IMPORTANCE Isolates of Cryptococcus gattii are currently causing an outbreak of cryptococcosis in western North America, and most of the cases occurred in the absence of coinfection with HIV. This pattern is therefore in stark contrast to the current global burden of one million annual cases of cryptococcosis, caused by the related species Cryptococcus neoformans, in the HIV/AIDS population. The genome sequences of two outbreak-associated major genotypes of C. gattii reported here provide insights into genome variation within and between cryptococcal species. These sequences also provide a resource to further evaluate the epidemiology of cryptococcal disease and to evaluate the role of pathogen genes in the differential interactions of C. gattii and C. neoformans with immunocompromised and immunocompetent hosts.